The Effect of Work Facilities and Motivation on Teacher Performance at SDIT Tunas Ilmu Tanjungpinang - Surya Kusumah (CV. Ridwan Publisher, 2023)
The purpose of this study was to determine the influence of work facilities and motivation on teacher performance at SDIT Tunas Ilmu Tanjungpinang. Teacher performance is the ability and effort of teachers to carry out learning tasks as well as possible in planning teaching programs, implementing learning activities and evaluating learning outcomes. This research uses quantitative methods. The research sample used was a saturated sample of 50 people. The data collection technique in this study was to use a 5-point likert scale in the form of a questionnaire with a total of 30 questions. The data analysis method is carried out using the validity test analysis method, reliability test, normality test, and hypothesis test. The results of this study show that work facilities affect teacher performance with a significant level (0.001 < 0.05), and motivation affects teacher performance with a significant level (0.000 < 0.05), the conclusion of this study is that there is an influence of work facilities and motivation together on teacher performance at SDIT Tunas Ilmu Tanjungpinang with a significant level (0.000 < 0.05).